Using evidence-based literature to inform and improve social work practice - Kidd, Kathryn, author; Morgan, George, advisor; Valentine, Deborah, advisor (Colorado State University. Libraries, 2009)
This study examined the use of professional evidence-based literature in informing practice, in knowledge-building, and in skill-building by MSW social workers practicing in Colorado Springs, Colorado. The study was a mixed methods study utilizing two survey phases: questionnaires and interviews. A brief questionnaire was distributed to 51 MSW social workers. This questionnaire included questions about the social worker's MSW degree, professional memberships, and journal subscriptions. It included the Brief Research Self-Efficacy Scale (Holden, Barker, Meenaghan, & Rosenberg, 1999) to determine comfort with specific research-related tasks. Analysis showed greater comfort on the part of participants with searching and reviewing the literature than with tasks more related to conducting research. Additionally, most scale items negatively correlated with years since receiving the MSW degree and correlated positively with the number of research courses taken. In the second phase, ten social workers were interviewed to obtain an in-depth understanding of their experiences with evidence-based professional literature. Interviewees were asked questions about what informs their decision-making about their practice, how they perceive the value of evidenced-based literature, their use of evidence-based literature, their perceived benefits of and barriers to the use of evidence-based literature, and what would make evidenced-based literature more useful/accessible to their practice. Three primary thematic areas were uncovered through the interviews. The value and use of evidence-based literature included a discussion of the concerns with reliance on evidence-based literature to determine best practice. Practitioner resources primarily included time issues and ways of obtaining information. While professional journal articles could be included as a resource, they were a major concern to the social workers interviewed and so were discussed separately. The issues surrounding practitioner use of professional literature, and especially practitioner needs with regard to their utilization of professional literature, are varied and complex. Numerous avenues for additional research in this area were identified. In addition, recommendations were made to facilitate the provision of greater support for social work practice and social work practitioners. Implications were discussed for social work education, professional social work journals, and social service agencies/organizations. Identifying ways to increase the use of evidence-based literature for social work practitioners is recommended.
Keywords: evidence-based literature; evidence-based practice; professional literature; social work; social work